2023
DOI: 10.1007/s00122-023-04372-4
|View full text |Cite
|
Sign up to set email alerts
|

The putative vacuolar processing enzyme gene TaVPE3cB is a candidate gene for wheat stem pith-thickness

Abstract: Key message The vacuolar processing enzyme gene TaVPE3cB is identified as a candidate gene for a QTL of wheat pith-thickness on chromosome 3B by BSR-seq and differential expression analyses. Abstract The high pith-thickness (PT) of the wheat stem could greatly enhance stem mechanical strength, especially the basal internodes which support the heavier upper part, such as upper stems, leaves and spikes. A QTL for PT in wheat was previously discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…The protein encoded by TRITD3BV1G280530 is a zinc finger protein, and its physical location is 829.1 Mb on chromosome 3BL of the durum wheat genome v1.0 [ 14 ]. Liu et al [ 15 ] found that a QTL for pith thickness in wheat was previously discovered on 3BL in a double haploid population of ‘Westonia’ × ‘Kauz’. A putative vacuolar processing enzyme gene TaVPE3cB was screened out as a potential pith-thickness candidate gene in Australian ‘Westonia’ wheat [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein encoded by TRITD3BV1G280530 is a zinc finger protein, and its physical location is 829.1 Mb on chromosome 3BL of the durum wheat genome v1.0 [ 14 ]. Liu et al [ 15 ] found that a QTL for pith thickness in wheat was previously discovered on 3BL in a double haploid population of ‘Westonia’ × ‘Kauz’. A putative vacuolar processing enzyme gene TaVPE3cB was screened out as a potential pith-thickness candidate gene in Australian ‘Westonia’ wheat [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [ 15 ] found that a QTL for pith thickness in wheat was previously discovered on 3BL in a double haploid population of ‘Westonia’ × ‘Kauz’. A putative vacuolar processing enzyme gene TaVPE3cB was screened out as a potential pith-thickness candidate gene in Australian ‘Westonia’ wheat [ 15 ].…”
Section: Introductionmentioning
confidence: 99%